2019
DOI: 10.1097/ta.0000000000002371
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological support interventions in trauma patients on mental health outcomes: A systematic review and meta-analysis

Abstract: BACKGROUND The recovery and rehabilitation of trauma survivors may be long and challenging. Patients may be prone to psychiatric disorders, cognitive impairments, and decreased quality of life. The objective of this review was to determine whether there is a role for psychological interventions in reducing the incidence and severity of psychiatric sequelae in trauma survivors. METHODS MEDLINE, PubMed, SCOPUS, and Google Scholar were searched for publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The subgroup meta‐analyses show that there were no significant effects of CBT on depression and anxiety. Our finding is consistent with a previous study, which reported that CBT for patients who experienced trauma did not reduce depression and anxiety significantly (Pham et al, ). In contrast, another study reported that CBT reduced depression significantly for the people with HIV and depression (Shi et al, ) and CBT has been suggested as an efficacious therapy in PTSD management (Cusack et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The subgroup meta‐analyses show that there were no significant effects of CBT on depression and anxiety. Our finding is consistent with a previous study, which reported that CBT for patients who experienced trauma did not reduce depression and anxiety significantly (Pham et al, ). In contrast, another study reported that CBT reduced depression significantly for the people with HIV and depression (Shi et al, ) and CBT has been suggested as an efficacious therapy in PTSD management (Cusack et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, another study reported that CBT reduced depression significantly for the people with HIV and depression (Shi et al, 2019) and CBT has been suggested as an efficacious therapy in PTSD management (Cusack et al, 2016). The inconsistent results of the previous research may be due to the differences in selected study participants (Pham et al, 2019), variability in the number of sessions and follow-up times (Kline, Cooper, Rytwinksi, & Feeny, 2018). Therefore, additional research should be conducted to verify the effectiveness of CBT for the homeless persons.…”
Section: Totalmentioning
confidence: 99%
“…Postinjury interventions might include informational and peer support, 36 or mental health initiatives to help decrease rates of PTSD, anxiety, and depression going forward, particularly in high-risk patients 37 . There is relatively sparse evidence in this realm, and a recent meta-analysis found no decrease in these disorders in trauma patients treated with cognitive behavioral theory-base interventions 38 . Certainly, further research into potential effective interventions is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why this model was not incorporated into subsequent major trauma policy documents and guidance. However, there is increasing evidence of effectiveness of stepped psychological and psychosocial approaches in major trauma care in terms of improving longer term outcomes 41 , reducing posttraumatic psychological distress symptoms and identifying those at risk of developing PTSD, anxiety and/or depression 41,42 .…”
Section: Models Of Psychological and Psychosocial Carementioning
confidence: 99%